Challenges of Integrating Islamic Religious Education Learning Based on Artificial Intelligence - Aldo Muhamad Derlan; Muhammad Zuhdi; Abdul Mukti (Pascasarjana IAIN Metro, 2026)
The integration of Artificial Intelligence (AI) into educational practices has brought about significant transformations in cross-disciplinary learning processes, including religious education. PAI which fundamentally emphasizes moral formation and spiritual development, faces serious challenges in adapting to AI-based learning environments. This study aims to examine the pedagogical, epistemological, and ethical implications of implementing AI-based PAI learning. This study uses a qualitative descriptive approach through a literature review by analyzing various literature related to AI in education, religious pedagogy, and technology ethics. The results of the study indicate that AI enables personalized learning according to individual learners' needs, increases learning accessibility, and supports the development of more interactive learning content and evidence-based data analysis for curriculum development. However, the main challenges relate to content accuracy, the ethical use of AI, and teacher readiness in integrating this technology into PAI learning. This article recommends strengthening teacher training and developing an adaptive PAI curriculum that aligns with the demands of Society 5.0 without neglecting the fundamental values ​​of Islamic education.